Cybercrime Dalam Perspektif Hukum Pidana Islam: Tantangan Formulasi Sanksi Di Era Digital - Ahmad Farid; Hajid Aflah al-Hafidz; Maulana Firmansyah; Saiin, Asrizal (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract: Cybercrime from the perspective of Islamic criminal law presents significant challenges in formulating appropriate sanctions in the digital era, particularly as the rapid development of information technology has generated new forms of crime that are not explicitly addressed in classical Islamic legal literature. This study aims to evaluate the extent to which the principles of Islamic criminal law can accommodate the phenomenon of cybercrime and how contemporary ijtihad can be applied to formulate fair and relevant sanctions. Using a normative legal approach through the analysis of classical and contemporary Islamic legal sources, this study finds the necessity of reformulating the concepts of jarīmah and ta‘zīr within the digital context to preserve the continued relevance of Islamic criminal law. This reformulation involves expanding the concept of jarīmah to include the protection of digital data as māl mutaqawwim (legally recognized property) and developing proportionate digital ta‘zīr sanctions based on the severity and impact of the offense. Such reformulation must remain aligned with the objectives of maqāṣid al-sharī‘ah the protection of religion, life, intellect, lineage, and property given that cybercrime poses significant threats to moral and social security. Therefore, the enforcement of Islamic criminal law should emphasize preventive and educational measures while also engaging constructively with positive law to establish a comprehensive and adaptive legal framework responsive to modern technological developments.Keywords: Cybercrime; Islamic Criminal Law; Ta’zir, Digital Era; Sanction Formulation Abstrak: Kejahatan siber dari perspektif hukum pidana Islam menghadirkan tantangan besar dalam merumuskan sanksi yang tepat di era digital, terutama karena pesatnya perkembangan teknologi informasi telah melahirkan bentuk-bentuk kejahatan baru yang tidak dibahas secara eksplisit dalam literatur klasik. Penelitian ini bertujuan mengevaluasi sejauh mana prinsip-prinsip hukum pidana Islam mampu mengakomodasi fenomena cybercrime serta bagaimana ijtihad kontemporer dapat diterapkan untuk merumuskan sanksi yang adil dan relevan. Dengan menggunakan pendekatan hukum normatif melalui analisis sumber-sumber hukum Islam klasik dan modern, penelitian ini menemukan perlunya reformulasi konsep jarimah dan ta’zir dalam konteks digital guna menjaga relevansi hukum Islam. Reformulasi tersebut dilakukan dengan memperluas konsep jarīmah pada perlindungan data sebagai māl mutaqawwim dan merumuskan sanksi ta‘zīr digital yang proporsional sesuai tingkat dampaknya. Reformulasi hukuman ini perlu selaras dengan maqāṣid al-syarī‘ah untuk menjaga agama, jiwa, akal, keturunan, dan harta, mengingat kejahatan digital juga mengancam keamanan moral dan sosial. Oleh karena itu, penegakan hukum Islam harus mengedepankan aspek preventif, edukatif, serta bekerja sama dengan hukum positif agar tercipta sistem hukum yang komprehensif dan adaptif terhadap perkembangan teknologi modern. Kata Kunci: Kejahatan Siber; Hukum Pidana Islam; Ta’zir; Era Digital; Perumusan